PENGARUH LAMA FERMENTASI TERHADAP KADAR ALKOHOL TAPAI PULUT PUTIH (Oryza Sativa Glutinosa) SEBAGAI RANCANGAN MODUL PADA KONSEP BIOTEKNOLOGI KONVENSIONAL KELAS XII SMA - Handayani Handayani; Imam Mahadi; Irda Sayuti (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2019)
Abstract: This study aims to study fermentation with alcohol content of tapai pulut putih (Oryza sativa glutinosa) based on conventional biotechnology concepts and fermentation time on alcohol content of tapai pulut putih (oryza sativa glutinosa) as a module designed on conventional biology class XII high school concepts. The research method consisted of two preparations, namely the making of Tapai Pulut Putih (Oryza sativa glutinosa) and the manufacture of a Biology High School module design. This research was conducted at the Laboratory of Biology Education Study Program FKIP University of Riau to produce white tapai pulut and measurements of alcohol content, temperature, and pH, starting in April to June 2018. This study used an experimental method with Completely Randomized Design (CRD) with 6 works and 3 results obtained 18 experimental planning. From the research conducted, it can be concluded that the duration of fermentation of white tapai pulut determines the alcohol content. The highest alcohol content at 42 hours fermentation time is equal to 0.75% while the duration of fermentation affects the decrease in the pH value of the substrate seen at 12 hours fermentation time, pH 4.80 and does not support changes in substrate temperature.Key Words: White Fermented Tofu, Alcohol, Conventional Biotechnology